Fracture mechanism of rock around a tunnel-shaped cavity with interconnected cracks under blasting stress waves - Li, Xiaohan; Zhu, Zheming; Wang, Meng; Xiao, Dingjun; Shu, Yun; Deng, Shuai (International journal of impact engineering, 2021)
•A new specimen with a tunnel-shaped cavity and interconnected cracks was proposed.•The incident direction of blasting stress waves affects crack initiation and propagation.•The RHT parameters of green sandstone can well characterise the dynamic response of rock.•Interconnected cracks greatly change stress distribution and fracture modes around tunnels. The existence of cracks in the surrounding rock significantly affects tunnel stability under dynamic disturbances. To study the fracture mechanism of tunnels in fractured rock masses under blasting stress waves, a new specimen, i.e., the specimen with a tunnel-shaped cavity and interconnected cracks (TCIC), was proposed in this paper. Using these specimens, blasting tests were conducted. The crack propagation data were monitored by crack propagation gauges (CPGs) and strain gauges (SGs). The Riedel-Hiermaier-Thoma (RHT) model was used to perform equal-scale numerical simulations on TCIC specimens. The stress distribution and fracture modes around the tunnel in a fractured rock mass under blasting stress waves were characterised. The results show that the interconnected cracks have an important influence on the dynamic response of the tunnel under blasting stress waves. The stress distribution around the tunnel remarkably changes due to the existence of the interconnected cracks, resulting in the initiation and propagation of these cracks, but there is no fracture on the tunnel boundary. The dynamic crack propagation behaviours are influenced by the incident direction of the blasting stress wave. The crack propagation velocity in the front blasting side of the tunnel is higher than that in the back blasting side. The research results are significant to the analysis of tunnel stability and the support design.